From Criminal to Crucial Participation: The Case of Dutch Volunteer Hackers - Anne Marte Gardenier (Social Inclusion)
Since the 1980s, Dutch volunteer hackers have been identifying and disclosing vulnerabilities in computer systems. Initially criminalized, these hackers now play a crucial role in Dutch cybersecurity governance. This article explores the transformation of hackers from criminals to crucial participants and examines what this case reveals about citizen participation in the digital age. The case study demonstrates that citizens can play a pivotal role in addressing challenges posed by digitization, although their contributions can remain unrecognized and constrained by hostile institutions. This article aims to deepen the understanding of various forms of citizen participation in digital society, how institutions can support or constrain them, and how citizens play a central role in shaping these institutions to legitimize their participation.